VALIDITAS MICHIGAN NEUROPATHY SCREENING INSTRUMENT VERSI BAHASA INDONESIA DALAM MENDETEKSI POLINEUROPATI DISTAL SIMETRIS DIABETIKA - Bintang, Andi Kurnia; Aulina, Susi; Goysal, Yudy; Amran, Muhammad Yunus; Hamid, Firdaus; Setiawan, Denise Dewanto (PERDOSNI, 2024)
Introduction: Distal Symmetric Polyneuropathy (DSPN) is the most common neuropathy subtype found in Diabetes Mellitus (DM) patients. Early screening is important to prevent complications. Michigan Neuropathy Screening Instrument (MNSI) was created in 1994 as an alternative screening tool for diabetic neuropathy. This instrument has not been validated in Indonesia. Aim: Assess validity and reliability of Indonesian version of MNSI in detecting diabetic DSPN. Methods: This cross-sectional study was done in Wahidin Sudirohusodo hospital, Makassar in December 2021-June 2022. Indonesian version of MNSI and Nerve Conduction Studies (NCS) was applied to subjects. Statistics were performed with Statistical Package for the Social Sciences (SPSS) version 25. Study protocol was approved by Health Research Ethics Committee, Faculty of Medicine, Hasanuddin University. Results: 102 subjects were eligible and divided into DM with DSPN (n=60) and DM without DSPN (n=42). Significant differences were found in age, body mass index, duration of DM diagnosis, treatment, HbA1c, Indonesian version of MNSI part B, and all NCS parameters (p<0,05). Area Under Curve (AUC) of part B was bigger than A (0,942 vs 0,606). Cut-off >=2,5 of part B had sensitivity, specificity, Positive Predictive Value (PPV), and Negative Predictive Value (NPV) of 95,0%, 90,5%, 93,4%, and 92,7%, respectively. Discussion: Cut-off >=2,5 for Indonesian version of MNSI part B was considered optimal. EMNG was recommended for DM patients with part B score >=2,5. Conclusion: Indonesian version of MNSI is a valid and reliable instrument to detect DSPN in Indonesian population. Keywords: diabetic neuropathy, DSPN, Indonesia, MNSI